The universality and effectiveness of labour law. Issue 3 (September 2019) - Ewing, Keith D; Hendy QC, John; Jones, Carolyn
This short article considers the Workers (Definition and Rights) Bill drafted by the Institute of Employment Rights as a possible solution to the intractable problem of employment status in the United Kingdom, to which Countouris and De Stefano refer. It does so in the context of ILO principles of 'universality' and 'effectiveness' of labour law, and three important ILO Declarations.